Rola podejścia facility management w oddziaływaniu na wartość nieruchomości i wartość przedsiębiorstwa - Półtorak, Bogusław (The Role of Facility Management in Corporate Real Estate Management, 2008)
In this paper, the author discussed the Corporate Real Estate Management. In modem economy a real estate sector is an important part of national resources. The real estete market is the part of capital market. Thus very essential is to estimate value of the real estate in objective way. This estimation could be more effective while we use facility management. The facility management raises value of real estate and increasing real estate value makes value of company higher.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 466-472